Surgical treatment of a persistent right aortic arch with concurrent patent ductus arteriosus in a 4‐month‐old German shepherd dog - Marco T. Duguay; Meagan A. Walker; Justyna Ostrowska; Katie L. Hoddinott (Veterinary Medicine and Science, 2023)
Abstract A 4‐month‐old intact female German shepherd dog was presented with a history of postprandial regurgitation, a palpably distended cervical oesophagus after eating, and poor weight gain despite a ravenous appetite. Computed tomography angiography, esophagoscopy and echocardiography identified a persistent right aortic arch with a concurrent patent ductus arteriosus (PDA) causing extraluminal oesophageal compression leading to marked segmental megaoesophagus. A heart murmur was not detectable. A left lateral thoracotomy was performed to ligate and transect the PDA without complication. The dog was discharged with mild aspiration pneumonia which resolved with antimicrobial therapy. Twelve months post‐surgery the owners reported no regurgitation.